Michelle Alperin : Sub Rosa. - Künstlerhaus Bethanien, Berlin; Philip Morris Kunstförderung, München; Art Center College of Design, Pasadena (Berlin : Künstlerhaus Bethanien Berlin, 2001)
This book appears on the occasion of Michelle Alperin's 2001 residency as a grantee of the Philip Morris Kunstförderung (Art Sponsorship) in the International Studio Programme of the Künstlerhaus Bethanien and the German premiere of the film Sub Rosa at the Eiszeit Cinema Berlin, December 9, 2001.
Duits
boek
Keywords: Alperin, Michelle